A Note on Coupled Dirac Operators - Hitchin, Nigel J. (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
The article considers some concrete solutions to the Dirac equation coupled to a vector bundle with connection, arising in the study of Yang-Mills equations and vector bundles on Riemann surfaces.